2016
DOI: 10.1051/shsconf/20163000031
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the main problems in social work with low-income families

Abstract: Abstract. Family is a basic social group, which influences one's life in all its stages. Through optimal fulfilment of functions which are imposed by society, it creates a safe environment for survival and development of family members. It is an essential factor in socializing and significantly affects the social functioning of its members. The family is also a dynamic system whose functioning operates a number of internal but also external factors. One of these factors is family income. The aim of our study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Low-income family in Malaysia refer to household that had income of less than RM3, 860 a month and also known as the B40 family [1]. Previous studies showed that family with low monthly income had low family functioning [2][3][4] and children with high socioemotional behaviour problems [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Low-income family in Malaysia refer to household that had income of less than RM3, 860 a month and also known as the B40 family [1]. Previous studies showed that family with low monthly income had low family functioning [2][3][4] and children with high socioemotional behaviour problems [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%